MID-SIZED TO LARGE-BODIED TERRESTRIAL MAMMALS - Sally Soo, Kaicheen; Melynda Cheok, Ka Yi; Joscha, Maiwald; Mohd Azlan, Jayasilan (UNIMAS Publisher, 2023)
Bornean tropical rainforests are home to 247 species of terrestrial mammals from 13 orders including 100 species of bats (Phillipps & Phillipps, 2016). Unfortunately, many of the tropical mammals in Sarawak exist in low population density due to forest conversion, logging, forest fire, illegal hunting, and wildlife trade, (Taylor et al., 1999; Bennett et al., 2002; Kinnaird et al., 2003; Sodhi et al., 2004; Heaney et al., 2005; Nakagawa et al., 2006; Linkie et al., 2007; Bernard et al., 2009; Gaveau et al., 2014; Brodie et al., 2015). To date, more ave been redlisted as species of global or regional conservation importance by the International Union for the Conservation of Nature (IUCN, 2020). This study categorized the mammals with more than 1 kilogram from the family Cercopithecidae, Manidae, Hystricidae, Ursidae, Mustelidae, Prionodontidae, Viverridae, Felidae, Elephantidae, Rhinocerotidae, Suidae, Tragulidae, Cervidae, and Bovidae as mid-sized to largebodied mammals (O’Brien, 2008; Tobler et al., 2008).